(1)
(f+g)(x) = 6x^2+2x-7+4x-3=6x^2+6x-10
(f-g)(x)=6x^2+2x-7-4x+3 = 6x^2-2x-4
(2)
(f+g)(x)=2x-3x+1-2x=-3x+1
(f-g)(x)=2x-3x-1+2x=x-1
Its just a matter of subbing
-7x - 4y = 6....subbing in (-2,2)...x = -2 and y = 2
-7(-2) - 4(2) = 6
14 - 8 = 6
6 = 6 (correct)
so ur solution is (-2,2)
Answer:
she earns $25.00 commission
Step-by-step explanation:
.05×500=25
<span>d = miles from the airport to home.
2.1*d+5=49.10 solve for d
d=</span>49.10-5/2.1 = 21 miles
Answer:
22%
Step-by-step explanation:
x/100 * 160=35
160x=3500
21.875
hence to the nearest percent: 22%